Cation disordering in ankerite as a function of Fe content - A. Zucchini; M. Masotta; M. Nazzari; M. Fastelli; P. Comodi (European Journal of Mineralogy)
Order–disorder transitions in minerals are of significance for technological applications and for the development of models that aid the understanding of the dynamics and composition of the Earth's interior. The present study investigates the effect of Fe content in ankerite, Ca(FexMg1−x)(CO3)2 (0 ≤x≥0.7<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="47pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="7e9f34f066117e7703372b3d8982d666"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-577-2025-ie00001.svg" width="47pt" height="11pt" src="ejm-37-577-2025-ie00001.png"/></svg:svg>, R<mover accent="true">3¯</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="17pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="859aee91089780fda1e5e9c75281293c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-577-2025-ie00002.svg" width="17pt" height="12pt" src="ejm-37-577-2025-ie00002.png"/></svg:svg> space group), on the distribution of cations in its crystal structure as a function of temperature. This investigation was conducted using ex situ experiments in a piston cylinder apparatus performed at 2–3 GPa and variable-temperature conditions (450–1000 °C). Crystal structure refinements, using single-crystal X-ray diffraction data, indicate that the temperature of the order–disorder phase transition in ankerite, when the space group changes from R<mover accent="true">3¯</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="17pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="f75e6c667c3f64f21a65bfc83826b4ad"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-577-2025-ie00003.svg" width="17pt" height="12pt" src="ejm-37-577-2025-ie00003.png"/></svg:svg> to R<mover accent="true">3¯</mover>c<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="fe064a2c9801a78cad20978a78c22cc9"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-577-2025-ie00004.svg" width="23pt" height="12pt" src="ejm-37-577-2025-ie00004.png"/></svg:svg>, is significantly influenced by the amount of Fe in the mineral's crystal structure, being full disordering conditions attained at 1000 and 800 °C in ankerites with x=0.3 and x=0.7, respectively. Prior to undergoing the order–disorder phase transition, it is shown that Fe exhibits a greater aptitude than Mg to exchange in the place of Ca (and vice versa). Mg, conversely, has a tendency to be bound at the M2 site or to exchange in smaller quantities than Fe. Furthermore, the significance of Fe as a parameter influencing the chemo-physical behavior of ankerite, as well as the temperature and character of the disordering process, is highlighted. This has the potential to significantly impact the mineral physics of ankerite under non-ambient conditions, particularly with regard to compressibility, phase stability, thermal and electric conductivity, and its role in the Earth's mantle geophysical modeling.